2003
DOI: 10.1080/13607860310001594691
|View full text |Cite
|
Sign up to set email alerts
|

Humor coping, health status, and life satisfaction among older adults residing in assisted living facilities

Abstract: The present study examined the relationships between humor coping, health status, and life satisfaction among older residents of assisted living facilities. A structural equation model with latent variables was specified for the three variables. Health status was expected to directly affect humor coping and life satisfaction. Humor coping was hypothesized to have a direct association with life satisfaction and indirectly affect the relationship between health status and life satisfaction. Participants complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 31 publications
5
40
0
10
Order By: Relevance
“…In a review of studies of the benefits of a sense of humor in mediating symptoms of physical illness, Martin (2001) reported few significant correlations between trait measures of humor and immunity, pain tolerance or self-reported illness symptoms. In contrast, Celso, Ebener and Burkhead (2003) reported a statistically significant relationship between health status and coping humor. Similarly, studies have shown associations between having a sense of humor and coping with life stress (Kuiper & Martin, 1993;Kuiper, Martin, & Dance, 1992;Lefcourt & Thomas, 1998;Newman & Stone, 1996;Overholser, 1992;Thorson & Powell, 1994;Thorson, Powell, Sarmany-Schuller, & Hampes, 1997).…”
Section: Sense Of Humor and Agingmentioning
confidence: 57%
“…In a review of studies of the benefits of a sense of humor in mediating symptoms of physical illness, Martin (2001) reported few significant correlations between trait measures of humor and immunity, pain tolerance or self-reported illness symptoms. In contrast, Celso, Ebener and Burkhead (2003) reported a statistically significant relationship between health status and coping humor. Similarly, studies have shown associations between having a sense of humor and coping with life stress (Kuiper & Martin, 1993;Kuiper, Martin, & Dance, 1992;Lefcourt & Thomas, 1998;Newman & Stone, 1996;Overholser, 1992;Thorson & Powell, 1994;Thorson, Powell, Sarmany-Schuller, & Hampes, 1997).…”
Section: Sense Of Humor and Agingmentioning
confidence: 57%
“…In the current study, Humor was one of predictors of systolic blood pressure. Humor is an emotion-oriented coping mechanism that is used to regulate emotional distress for unchangeable problematic situations (Celso et al 2003). Humor has the effect of modifying (Fry 1994) and reappraising (McCrae 1984) stressors.…”
Section: Discussionmentioning
confidence: 99%
“…A cursory review of some of the relevant literature on the relationship between emotion-focused coping and health indicates that humor, often used to reappraise a stressful situation [16], had good potential for being related to older women's health outcomes, based on findings on other populations. Indeed, researchers have related humor to better physical health among both cancer patients [17] and older adults residing in assisted living facilities [16].…”
Section: Introductionmentioning
confidence: 99%